How much oxygen desaturation occurs in healthy people hiking at simulated altitude? - Bushman, Timothy (My University, 2010)
Arterial de-saturation often occurs during heavy exercise at altitude. This may be of concern in cardiac patients who desire to perform recreational activity (e.g., hiking) at altitude as it may provoke exertional ischemia. The purpose was to determine whether exercise intensity is appropriately regulated during hiking. Healthy physically-active young adults performed three exercise bouts of 21 min duration including a warm-up and a 'hiking' period: 1) a sea level (SL) hike at an intensity approximating the ventilator threshold, 2) a high altitude F1O2=16.5%) (-6,000 feet) hike at the same absolute intensity, and 3) a high altitude hike with the freedom to reduce or increase ambulatory speed during the 'hike.' At SL, Altitude Fixed Speed and Altitude Variable Speed, the HR was 164.2, 169.2 and 166.6 bpm, RPE was 5.2, 5.8 and 4.5, % saturation by pulse oximetry was 94.8, 87.4 and 87.8% and final speed was 4.0, 4.0 and 3.88 mph, respectively. Despite experiencing significant de-saturation at simulated altitudes, subjects did not display a tendency to regulate exercise intensity to protect from arterial de-saturation. The results suggest that cardiac patients may need education or counseling in order to adequately protect themselves if they plan to hike at altitude.
Keywords: Oxygen in the body -- Measurement; Altitude, Influence of; Hiking -- Physiological aspects